Inventory of Epiphytic Lichen Foliose on Tea Plants in Ngargoyoso, Karanganyar, Central Java - Irnawati, Dika Dwi; Roziaty, Efri (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Lichen is a combined organism between algae and fungi. Lichen has various body shapes, one of which is foliose. Lichen is found living epiphytic on the stems of tea plants. This study aims to determine the types of epiphytic lichen foliose on tea plants in Ngargoyoso, Karanganyar, Central Java. The method used is an exploratory method with purposive sampling techniques. Sampling was carried out at three stations with different altitudes. Station 1 (900 m asl), Station 2 (1.000 m asl), and Station 3 (1.100 m asl). The study results obtained a number 12 species of lichen foliose consisting of Parmotrema tinctorum (Delise ex Nyl.) Hale, P. austrosinense (Zahlbr.) Hale, P. reticulatum (Taylor) M. Choisy, P. hypotropum (Nyl.) Hale, P. perlatum (Huds.) M. Choisy, Flavoparmelia soredians (Nyl.) Hale, F. caperata (L.) Hale, Hypogymnia physodes (L.) Nyl, Physcia stellaris (L.) Nyl, P. aipolia (Ehrh. ex Humb.) Fürnr, Heterodermia japonica (Satō) Swinscow & Krog, and Dirinaria applanata (Fée) D.D. Awasthi. The most dominant species found at all three stations were Parmotrema austrosinense (Zahlbr.) Hale with a total of 104 colonies. The least encountered species was Physcia stellaris (L.) Nyl with a total of 3 colonies.